Two-Period Reputation Model of Knowledge Sharing between Enterprises Based on Signal Game Analysis. (13th April 2021) - Wang, Qiliang; Jiang, Qingquan; Yu, Hongxia; Fu, Rong; Mo, Changwei
Abstract : Knowledge sharing between enterprises is an important way to obtain external research and development (R&D) resources and keep competitiveness. This paper used a reputation model based on a two-period signal game to explore knowledge-sharing micromechanism between enterprises and key influencing factors of enterprises. The results show that reputation effects are an important mechanism that will make knowledge sharing between enterprises operate effectively. Motivated by reputation effects, even those noncooperative enterprises continue to pretend to be cooperative enterprises for knowledge sharing before the end of the game. Finally, we adopt the analytical methods and conclusions given by the model in this article to analyze opportunistic problems in knowledge sharing among cooperative enterprises and put forward some valuable suggestions on the conditions for the effective use of corporate reputation effects.